Potensi Pengembangan Olahan Kuda Sebagai Oleh Oleh Desa Pearung Kabupaten Humbang Hasundutan - Trisnawaty, Trisnawaty (Jurnal Akademi Pariwisata Medan, 2024)
The development of processed horse meat as a typical souvenir from Pearung Village, Humbang Hasundutan Regency is an interesting step to introduce the richness of local culinary and culture to tourists and the wider community of Pearung Village, like most areas in Humbang Hasundutan has great potential to develop processed horse meat products because it has a strong livestock tradition and a community skilled in food processing. By combining community empowerment efforts, tourism promotion and product quality monitoring, Pearung Village can develop high-quality processed horse meat and become a famous souvenir from Humbang Hasundutan Regency. Several factors that influence consumer preferences for consuming processed horse meat such as health factors, psychological factors and personal factors. This study aims to make horse meat a typical souvenir from Pearung Village, Humbang Hasundutan Regency. Tourism is one of the utilization of natural resources that can have high economic value for an area that manages natural resources into tourist attractions that can attract visitors both from within and outside the country, in addition to having high economic value and being able to absorb labor. And encourage development. Investment, tourism can grow and increase pride in the nation so that people who care more about a nation will grow. However, development of tourist attraction areas has not been carried out in several tourist areas.